2017
DOI: 10.1155/2017/1958947
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin Triggers Anorexia and Body Weight Loss through Regulating the Inflammatory Response in the Hypothalamic Microglia

Abstract: Visfatin is an adipokine that is secreted from adipose tissue, and it is involved in a variety of physiological processes. In particular, visfatin has been implicated in metabolic diseases, such as obesity and type 2 diabetes, which are directly linked to systemic inflammation. However, the potential impacts of visfatin on the hypothalamic control of energy homeostasis, which is involved in microglial inflammation, have not fully been investigated. In this study, we found that treatment with exogenous recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In particular, adipose tissue dynamically communicates with the hypothalamus through its own chemical messengers termed adipokines [17,18]. Notably, the circulating levels of most adipokines are proportional to adiposity and long-term elevation of adipokines elicits adverse effects, such as inflammation, oxidative stress, and endoplasmic reticulum stress, which might comprise potential pathogenic elements for the development of metabolic disorders [19].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, adipose tissue dynamically communicates with the hypothalamus through its own chemical messengers termed adipokines [17,18]. Notably, the circulating levels of most adipokines are proportional to adiposity and long-term elevation of adipokines elicits adverse effects, such as inflammation, oxidative stress, and endoplasmic reticulum stress, which might comprise potential pathogenic elements for the development of metabolic disorders [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies and our study both observe that OVX mice, an experimental mouse model for menopause, displayed visceral obesity showing increased body weight and adiposity [ 29 ]. Moreover, numerous studies have reported that sustained elevation of substances derived from visceral fats triggers hypothalamic inflammation concomitant with reactive gliosis [ 30 , 31 ]. In agreement with this, we successfully confirmed that OVX mice showed elevated hypothalamic inflammation by analyzing the expression of genes involved in cellular inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia do have an established role in the anorexia associated with sickness behaviour: the collective fever, withdrawal, and appetite suppression that is seen in response to neuroimmune challenge . Microglia are likely to be involved in all aspects of this response, and microglial activation with visfatin or TLR2 activation leads to increases in pro‐opiomelanocortin (POMC) neuronal activity and a suppression of food intake co‐incident with other aspects of the sickness response …”
Section: The Role Of Microglia In Satietymentioning
confidence: 99%
“…96 Microglia are likely to be involved in all aspects of this response, and microglial activation with visfatin or TLR2 activation leads to increases in pro-opiomelanocortin (POMC) neuronal activity and a suppression of food intake co-incident with other aspects of the sickness response. 97,98 Microglia may also be involved in the dysregulated appetite associated with obesity. Microglial activation is a key factor in obesity and can be seen in the brain prior to evidence of peripheral inflammation.…”
Section: Microglia In Satiety In Sickness and Obesitymentioning
confidence: 99%
See 1 more Smart Citation